Clinical and pathogenic features of ETV6 -related thrombocytopenia with predisposition to acute lymphoblastic leukemia - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica (Roma), 2016)
ETV6-related thrombocytopenia is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematologic malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 patients with ETV6-related thrombocytopenia from seven pedigrees. They have five different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-related thrombocytopenia was 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of the patients with ETV6-related thrombocytopenia were mild, but four subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly higher incidence of this condition compared to that in the general population. Clinical and laboratory findings did not identify any particular defects that could lead to the suspicion of this disorder from the routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelets were not enlarged. In vitro studies revealed that the maturation of the patients' megakaryocytes was defective and that the patients have impaired proplatelet formation. Moreover, platelets from patients with ETV6-related thrombocytopenia have reduced ability to spread on fibrinogen. Since the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are also characterized by normal platelet size and predispose to hematologic malignancies, we suggest that screening for ETV6, RUNX1 and ANKRD26 mutations should be performed in all subjects with autosomal dominant thrombocytopenia and normal platelet size.